2018
DOI: 10.1039/c8md00481a
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological activity of novel ammonium salts containing sterically hindered phenolic fragment and phosphoryl group

Abstract: Novel multifunctional ammonium salts was obtained with high antimicrobial, antioxidant and low cytotoxic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies, including our own, have focused on elucidating structure–activity relationships (SARs) and structure–resistance relationships (SRRs) to enable the rational design of novel QAC compounds. These studies provided insights into the number and ratio of charges, length and types of side chains, core structural rigidity, and the inclusion of organometallic substituents have all contributed to the advancement of discovering next-generation QAC scaffolds. , …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including our own, have focused on elucidating structure–activity relationships (SARs) and structure–resistance relationships (SRRs) to enable the rational design of novel QAC compounds. These studies provided insights into the number and ratio of charges, length and types of side chains, core structural rigidity, and the inclusion of organometallic substituents have all contributed to the advancement of discovering next-generation QAC scaffolds. , …”
Section: Introductionmentioning
confidence: 99%
“…In our opinion, the combination of a phenolic substituent, a hydrazone moiety and an ammonium center in one molecule will solve the problem of the solubility of the target compounds in water along with high antioxidant and antimicrobial activities. The development of this study is based on our ongoing work on the design, synthesis and evaluation of the biological activity of positively charged isatin‐3‐acylhydrazones, and spatially hindered phenols . Our previous results showed that compounds containing a bulky phenolic fragment showed the best activity against Staphylococcus aureus ( Figure ) …”
Section: Introductionmentioning
confidence: 99%